Determinan Penyerapan Tenaga Kerja di Pulau Sumatera dan Pulau Jawa - Yenni Anggrya; Emi Maimunah (Departement of Mathematics Education, 2024)
Labor absorption is the opening up of greater employment opportunities to provide more job opportunities for the working age population. Job opportunities that are already filled can be seen in the number of people who are already working. The aim of this research is to look at the influence of the Provincial Minimum Wage, Labor Productivity, and Gross Fixed Capital Formation on Labor Absorption on the Islands of Sumatra and Java. Secondary data used in this research comes from the Central Statistics Agency and the Ministry of Manpower. The method used in this research is the Ordinary Least Square (OLS) method and uses panel data with 80 studies with a research period of 2018-2022. The results of the research show that the Provincial Minimum Wage and PMTB have a positive and significant influence on labor absorption on the islands of Sumatra and Java. Meanwhile, labor productivity has a negative and significant influence on labor absorption on the islands of Sumatra and Java.